Level of Knowledge and Nutritional Attitudes of Consumers of Packaged UHT Milk in Lamongan Regency - M Riyanto; Vivi Indriani; Wahyudi Himawan Sutanto (Talenta Publisher, 2024)
UHT milk is a food commodity that plays an important role in fulfilling calcium nutritional sources. UHT milk consumption practices can be influenced by consumer nutritional knowledge. The general objective of this study was to analyze the relationship between nutritional knowledge and the characteristics of UHT milk consumers in Lamongan Regency and the relationship between nutritional knowledge and consumer nutritional attitudes. Sampling was carried out based on the calculation of the Slovin formula and obtained the number of 100 respondents. Data were analyzed descriptively and correlation test was performed. The results obtained as many as 77% of respondents have sufficient knowledge of nutrition. The nutritional attitude of the respondents showed that 63% of the respondents had adequate nutrition attitudes. The conclusion of this study is that there is a significant relationship between the education variable and the job characteristics of the respondents and their knowledge of nutrition. The test results of the relationship between nutritional knowledge and nutritional attitudes showed that there was a very significant and direct relationship between nutritional knowledge and nutritional attitudes